2020
DOI: 10.1111/febs.15276
|View full text |Cite
|
Sign up to set email alerts
|

Heat‐Shock protein A12A is a novel PCNA‐binding protein and promotes hepatocellular carcinoma growth

Abstract: Hepatocellular carcinoma (HCC) is a leading cause of cancer-related death. Proliferating cell nuclear antigen (PCNA) plays a pivotal role in cancer development and progression. However, the long-term dismal prognosis of HCC mandates more investigation to identify novel regulators in HCC pathogenesis. Heat-shock protein A12A (HSPA12A) encodes a novel member of the HSP70 family. Here, we report that HCC cells showed increased HSPA12A expression, and overexpression of HSPA12A promoted HCC growth and angiogenesis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 41 publications
1
9
0
Order By: Relevance
“…The Akt activation in RCC cells was also not affected by HSPA12A ( Figure S19 ). When taken into account that our recent reports have shown a promoted proliferation of hepatocellular carcinoma cells by HSPA12A 53 , the current data suggest that the effects of CD147 and HSPA12A on proliferation are cancer cell type- and signaling activation-dependent.…”
Section: Discussionsupporting
confidence: 51%
“…The Akt activation in RCC cells was also not affected by HSPA12A ( Figure S19 ). When taken into account that our recent reports have shown a promoted proliferation of hepatocellular carcinoma cells by HSPA12A 53 , the current data suggest that the effects of CD147 and HSPA12A on proliferation are cancer cell type- and signaling activation-dependent.…”
Section: Discussionsupporting
confidence: 51%
“…Subsequent studies revealed the downregulation of HSPA12A in the brains of patients with schizophrenia [17]. Recently, we have reported that HSPA12A is necessary for cerebral protection from stroke, for development of obesity and nonalcohol liver disease, and for growth of liver cancer [18][19][20][21]. Particularly, we found that HSPA12A facilitates angiogenesis in mouse liver carcinoma [21] and increases basal levels of ERK phosphorylation and VEGF expression in endothelial cells [21,22].…”
Section: Introductionmentioning
confidence: 70%
“…Recently, we have reported that HSPA12A is necessary for cerebral protection from stroke, for development of obesity and nonalcohol liver disease, and for growth of liver cancer [18][19][20][21]. Particularly, we found that HSPA12A facilitates angiogenesis in mouse liver carcinoma [21] and increases basal levels of ERK phosphorylation and VEGF expression in endothelial cells [21,22]. Therefore, it is possible that HSPA12A might promote angiogenesis to attenuate post-MI cardiac dysfunction.…”
Section: Introductionmentioning
confidence: 80%
“…Its synthesis and expression can reflect the proliferation of tumor cells. A significant increase in PCNA in HCC cells often accelerates cell proliferation, and the balance between cell proliferation and apoptosis is broken ( 38 ). Here, we show that both Huh7-derived exosomes and overexpressed miR-4800-3p obviously increased PCNA expression and finally promoted HCC cell proliferation and tumor growth.…”
Section: Discussionmentioning
confidence: 99%